Diagnostics turbocompressors of diesels engine at running using repair and restoration compositions - S. A. Kornilovich; D. N. Algazin; G. V. Redreev; A. N. Rusanov (Вестник СибАДИ)
The article dwells upon the importance of increasing reliability of turbocompressors of internal combustion engines. There is a suggestion on causes of increased wear of the unit’s bearings. There are set the problems of improving the wear resistance of the unit using repair and restoration compositions (RRC) at the stage of the running. To assess the quality of repair and to determine the completion’s moment of processing RRC unit the use of vibro-acoustic method of diagnostics is justified.